Molecular autopsy: Twenty years of post-mortem diagnosis in sudden cardiac death - Martínez-Barrios, Estefanía; Grassi, Simone; Brión, María; Toro, Rocío; Cesar, Sergi; Cruzalegui, José; Coll, Mònica; Alcalde, Mireia; Brugada, Ramon; Greco, Andrea; Ortega-Sánchez, María Luisa; Barberia, Eneko; et al. (Frontiers in Medicine, 2023)
In the forensic medicine field, molecular autopsy is the post-mortem genetic analysis performed to attempt to unravel the cause of decease in cases remaining unexplained after a comprehensive forensic autopsy. This negative autopsy, classified as negative or non-conclusive, usually occurs in young population. In these cases, in which the cause of death is unascertained after a thorough autopsy, an underlying inherited arrhythmogenic syndrome is the main suspected cause of death. Next-generation sequencing allows a rapid and cost-effectives genetic analysis, identifying a rare variant classified as potentially pathogenic in up to 25% of sudden death cases in young population. The first symptom of an inherited arrhythmogenic disease may be a malignant arrhythmia, and even sudden death. Early identification of a pathogenic genetic alteration associated with an inherited arrhythmogenic syndrome may help to adopt preventive personalized measures to reduce risk of malignant arrhythmias and sudden death in the victim’s relatives, at risk despite being asymptomatic. The current main challenge is a proper genetic interpretation of variants identified and useful clinical translation. The implications of this personalized translational medicine are multifaceted, requiring the dedication of a specialized team, including forensic scientists, pathologists, cardiologists, pediatric cardiologists, and geneticists.